Types of synonymous words and their places of use - Rustamova Davlatxon Toyirjon qizi (Open Academia, 2023)
This article explores the various types of synonymous words and their respective applications in different contexts. Synonyms are essential linguistic elements that enable writers and speakers to convey similar meanings through diverse lexical choices. The study analyzes the nuances between synonyms and investigates the specific environments where certain synonyms are best suited. By understanding the subtle distinctions in meaning, readers and language learners can enhance their communication skills and develop a more nuanced language repertoire.